Environmental, Social and Governance (ESG) risk, uncertainty, and the mining life cycle - Maybee, Bryan; Lilford, Eric; Hitch, Michael (Elsevier, 2023)
Companies are facing increasing pressure from investors, customers and regulators to address, monitor and manage Environmental, Social and Governance (ESG) risk. Asset owners, such as private equity firms, particularly in the minerals sector are increasingly concerned with the way that asset managers manage ESG risk for corporate finance activities such as acquisitions, to protect value and even unleash value over the asset holding life. Common ESG risks include those related to climate change impact mitigation, environmental practices and duty of care. From a social and governance risk perspective, elements may include respect for human rights, anti-bribery and corruption practices, as well as compliance to relevant laws and regulations. Although some ESG risk elements remain constant over the asset holding period, others may be more fluid, and in this paper, we embrace the notion of uncertainty and a broader acceptance and comfort in the unknown.